Retrospective study of chidamide-containing regimens as maintenance therapy among T- and NK-cell lymphoma patients - Hai, Tao; Wu, Wanchun; Ren, Kexin; Li, Na; Zou, Liqun (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to explore the efficacy of chidamide-containing regimens as maintenance therapy in patients with T- and natural killer (NK)-cell lymphomas (TNKLs).MethodsA total of 51 patients with TNKLs who received chidamide-containing regimens after induction therapy were enrolled. The primary end point was progression-free survival (PFS), while the secondary end point was overall survival (OS) and safety.ResultsThe median duration of maintenance was 14 months (range = 1–24 months). Most of the patients were diagnosed with extranodal NK/T-cell lymphoma (ENKTCL; 24/51, 47.1%), followed by angioimmunoblastic T-cell lymphoma (AITL; 14/51, 27.5%). The median PFS and OS were 21 and 29 months, respectively. The 2-year PFS and OS among the overall population were 45.1% and 54.2%, respectively. Patients who experienced complete remission (CR) after induction therapy had favorable survival compared with non-CR patients (partial remission/stable disease, PR/SD). Patients who experienced CR after first-line induction treatment also had favorable survival, but similar significance was not observed in the salvage treatment group. Although 86.3% of the patients had chidamide-related adverse events (AEs), severe hematological AEs (grade ≥3) occurred in only 11 (21.6%) patients, indicating the safe toxicity profile of chidamide.ConclusionThe prolonged survival indicated that chidamide-containing maintenance therapy is promising and well tolerated in patients with TNKLs.